Alonso Cano según Lázaro Díaz del Valle - Riello Velásco, José María (Anales de Historia del Arte, 2007)
This article explains some reflexions about Alonso Cano’s life, which was written by Lázaro Díaz del Valle in the middle of 1658, with particulary attention to his arquitectonical works.